The Effect of Customer Relationship Management on Customer Retention at KMU Gresik Eye Clinic - M. Azzam Rabbani (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
Knowing and analyzing customer engagement, customer bonding and customer satisfaction on customer retention at the KMU eye clinic. This research was conducted using a quantitative research method approach. The population in this study was the KMU Mata Utama Clinic Customers as many as 350 people, this number was obtained from the five research indicators multiplied by five. The sample in this study were 93 respondents. By using Multiple Linear Regression Analysis. The results showed that Customer Engagement has no significant effect on Customer Retention, Bonding Customer has no significant on Customer Retention and Customer Satisfaction has an effect on Customer Retention.